PERENCANAAN STRATEGIS SISTEM INFORMASI (STUDI KASUS : CV XYZ) - Septi Putri; Afifah Azzahra; Yohanes Agung Apriyanto; Andri Wijaya (Jurnal Sistem Informasi (JUSIN), 2024)
In today's rapidly evolving digital era, information systems (IS) play a crucial role in supporting business operations, especially in trading and distribution companies like CV XYZ. CV XYZ specializes in the distribution of fast-moving consumer goods (FMCG), such as snacks, beverages, and confectionery products. To enhance operational efficiency, strategic information system planning is essential to align IS/IT investments with long-term business goals.this study aims to develop an IS strategic plan for CV XYZ to optimize business operations and improve competitiveness. Using a qualitative approach, data collection involved interviews and literature reviews. Analytical methods, including PESTLE, SWOT, and Gap Analysis, were employed to evaluate internal and external factors influencing the company's IS/IT needs.Key findings indicate that CV XYZ requires an integrated information system to manage inventory, transactions, and financial reporting in real time. Recommended strategies include implementing Customer Relationship Management (CRM) systems, enhancing data security, expanding IT infrastructure, and developing cloud-based solutions. The proposed roadmap outlines a phased IS/IT implementation over 3–5 years, emphasizing the integration of existing applications with advanced technologies to support sustainable growth.The study concludes that strategic IS planning enables CV XYZ to address operational challenges, leverage digitalization opportunities, and improve customer satisfaction. Recommendations include enhancing system integration, upgrading cybersecurity measures, and fostering strategic partnerships to achieve competitive advantages and adapt to market dynamics.